2015
DOI: 10.5851/kosfa.2015.35.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Bifidobacteria and Carbohydrate Metabolism

Abstract: In recent years, the knowledge about bifidobacteria has considerably evolved thanks to recent progress in molecular biology. The analysis of the whole genome sequences of 48 taxa of bifidobacteria offers new perspectives for their classification, especially to set up limit between two species. Indeed, several species are presenting a high homology and should be reclassified. On the other hand, some subspecies are presenting a low homology and should therefore be reclassified into different species. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…This species possesses the genetic machinery suggesting some ability to synthetize specific enzymes for BMO degradation, as highlighted by the presence of genes coding for β-galactosidase and α- or β-glucosidase, genes also present in other bacteria such as B. bifidum, B. longum subsp. infantis, B. mongoliense, B. biavatii, B. kashiwanohense , and B. stellenboschense (Delcenserie et al, 2007 ; Milani et al, 2014 , 2015 ; Bondue and Delcenserie, 2015 ). B. bifidum BBA1 grew as well on medium containing 3′SL as the main carbohydrate source.…”
Section: Discussionmentioning
confidence: 99%
“…This species possesses the genetic machinery suggesting some ability to synthetize specific enzymes for BMO degradation, as highlighted by the presence of genes coding for β-galactosidase and α- or β-glucosidase, genes also present in other bacteria such as B. bifidum, B. longum subsp. infantis, B. mongoliense, B. biavatii, B. kashiwanohense , and B. stellenboschense (Delcenserie et al, 2007 ; Milani et al, 2014 , 2015 ; Bondue and Delcenserie, 2015 ). B. bifidum BBA1 grew as well on medium containing 3′SL as the main carbohydrate source.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, infants with a Bifidobacteria dominated microbiota have been shown to have less fucosylated oligosaccharides in their faecal samples compared to infants with Bacteroides dominated microbiota, suggesting the former’s preference for fucosylated oligosaccharide consumption [ 12 ]. In general terms, bifidobacterial genomes contain fewer genes encoding for the breakdown of complex polysaccharides [ 34 ] consistent with their preference for the degradation of HMOs, starch and starch hydrolysates, with the dietary intake of starch at 9 months of age having been shown to be positively correlated with the abundance of Bifidobacteria spp. [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic and protein modelling studies have recently suggested that the bifidobacterial XFPK enzyme is related to that found in members of the Coriobacteriales order and that xfpK was horizontally transferred between (an ancestor of) these two groups 21,28,29 . Another interesting difference between bifidobacteria (and now possibly Coriobacteriales) and other bacteria is that they lack a number of enzymes, such as phosphofructokinase, which are crucial to control central carbohydrate metabolism 30 .…”
Section: Introductionmentioning
confidence: 99%